(untitled) - Seidensticker, Edward (New York, 1990)
As this vibrant, intimately detailed volume opens in September 1923, Tokyo is rebuilding after a devastating earthquake and fires; Japan is run by the Taisho emperor, a mentally incapacitated figurehead. Tokyo would rebuild a second time: after the Allied bombing raids of WW II and the typhus plague of 1945-46. By the book's close, the city is the hub of a contemporary Japan that has largely overcome strong feelings of inferiority; yet it is still a very insular town, one that effectively excludes foreigners from much of its pulsating life. This sequel to Low City, High City is much more than a portrait of Tokyo; in good measure, it is a serendipitous social history of modern Japan. Interwoven with 72 photographs, the narrative covers sundry topics from nightlife to the arts, all set in the context of Japan's metamorphosis from 1930s jingoistic, repressive state to its emergence as the world's chief creditor nation.